Schädliche Cossidae an Obst- und Forstgehölzen und ihre Bekämpfung in Bulgarien (Lepidoptera: Cossidae). - Sengalewitsch, Georgi (Contributions to Entomology = Beiträge zur Entomologie, 1966)
Zeuzera pyrina Linnaeus and Cossus cossus cossus Linnaeus cause economically significant damage in Bulgaria. The present paper discusses their injurious effect on various species of wood. Data about phenology, fertility, appearance of damage, control and natural enemies of these two injurious insects are given. Cossus cossus cossus Linnaeus showed a more rapid development in species of wood with a higher sugar content. The caterpillars were successfully bred in apple fruit.